Immunosuppressive properties of sera and urine dialysates from kidney-graft recipients treated with azathioprine, prednisolone, and niridazole. Issue 6090 (24th September 1977) - Jones, B M; Bird, M; Massey, P; Millar, D; Miller, J J; Reeves, S; Salaman, J R
Abstract : Niridazole, an antischistosomal agent, was given to renal transplant recipients in addition to azathioprine and prednisolone, as there is experimental evidence that this combination of drugs is highly immunosuppressive. Sera obtained from kidney-graft recipients during the first two weeks after transplantation were examined for their ability to inhibit the one-way mixed lymphocyte reaction (MLR). Sera from seven patients receiving azathioprine, prednisolone, and niridazole (triple-drug treatment), five patients receiving azathioprine and prednisolone, and two other patients treated with niridazole alone for schistosomiasis produced MLR inhibition by comparison with pretreatment (control) sera. A mean of 78% inhibition was observed with sera taken after one day's treatment with the three-drug combination, whereas this level of in-vitro immunosuppression occurred only after eight days of treatment with azathioprine and prednisolone. Niridazole alone produced an effect similar to azathioprine and prednisolone. Concentrated dialysate of urine from a patient receiving triple-drug treatment not only inhibited the MLR but also significantly prolonged the survival of heterotopic heart allografts in rats, whereas dialysate from the same patient after niridazole had been stopped gave less MLR inhibition and failed to prolong heart allograft survival. Since niridazole thus increased the in-vitro and in-vivo immunosuppressive action of azathioprine and prednisolone, we suggest that this triple-drug combination might be useful for preventing early acute kidney graft rejection.